The Urgency of Educational Management in Developing Islamic Educational Institutions - Rosmawati, Rosmawati; Harahap, Nasruddin (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This research aims to explain the urgency of developing Islamic educational institutions. This type of research is qualitative with a Library Research approach. The research data is in the form of data about the urgency of educational management, Islamic educational institutions from primary sources in educational form management books, Islamic educational institutional development books, and relevant journals. Data collection techniques were carried out using documentation studies. The researchers' data sources were obtained from books and journals about the urgency of educational management in Islamic educational institutions. Data analysis uses Content Analysis. Based on the research results, it was found that educational management has a very important urgency in developing educational institutions. The urgency of educational management in developing educational institutions includes Improving the Quality of Education, Resource Efficiency, Planning Strategy, Providing an Optimal Learning Environment, Human Resource Development, Evaluation, and Continuous Improvement, which are called Educational Goals. Thus, educational management is a very important foundation in developing educational institutions so that they can provide quality, efficient education in line with the demands of the times. Thus, this conclusion shows that Islamic education management in developing educational institutions can make a positive contribution to creating better educational institutions.